University of the Philippines Post Office a production systems study - Ang, Richard; Mercado, Mary Jane.; Rivera, Maria Ruby. (Diliman, Quezon City College of Engineering, 1992)
With the common sentiment regarding the inefficiency of the postal system of the Philippines, the group decided to study the University of the Philippines Post Office. After a thorough study of the existing system, we discovered a number of problems e.g. manpower shortage, rampant absenteeism, lack of discipline, unstable materials procurement, poor layout, etc. In view of alleviating the present condition, the group has recommended the follov/ing courses of action; Implement stricter penalties for tardiness and absenteeism, implement programs that will improve camaraderie and promote a team spirit among the employees, revise the current organizational structure, use visual aids to remind employees and the mailing public regarding existing policies, maintain a steady number of regular employees, increase the fixed accountability of the office by 30%, maximise use of metered machines, Employ Winter's forecasting method in inventory, management of stamps and capacity planning to determine number of casuals, increase number of mail boxes within the U.P. Diliman Campus modify the current layout to ease traffic within the Office and relocate stamps and metered machine windows to make room for queues.
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: University of the Philippines Post Office; Postal service; Production engineering